2005
DOI: 10.1080/13506120500032394
|View full text |Cite
|
Sign up to set email alerts
|

Relative transcriptional activities ofSAA1promoters polymorphic at position −13(T/C): Potential association between increased transcription and amyloidosis

Abstract: The risk associated with the serum amyloid A (SAA) 1 gene and developing AA-amyloidosis is still controversial. In familial Mediterranean fever or Caucasoid rheumatoid arthritis (RA), the SAA1.1 allele is a risk factor for the development of AA-amyloidosis. However, individuals with the SAA1.3 allele are susceptible to AA-amyloidosis in the Japanese RA population, but those with the SAA1.1 are not. Previous reports have indicated that the -13T/C single nucleotide polymorphism (SNP) at the 5'-flanking region of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 26 publications
1
21
0
2
Order By: Relevance
“…Recently, the association between SAA1 -13T and amyloidosis in Japanese RA patients has been suggested to be the result of an increased transcriptional activity of the gene. 23 Therefore, our data strongly support the notion that the previously reported associations between the SAA1.3 allele and amyloidosis may be accounted for by a strong linkage between -13T and 2995C in the SAA1 gene in Japanese 23,24 Our data also indicate that examining both of the polymorphisms may be more useful than examining just one of them for estimating the risk of the development of amyloidosis. However, because pairwise linkage disequilibrium between polymorphic loci in this gene and the magnitude of the association between these markers and SAA levels have been reported to vary depending on ethnicity, it remains to be seen if the effect of the genetic variant investigated in this study is observed in other ethnic groups to confirm the results of the present study.…”
Section: Discussionsupporting
confidence: 85%
“…Recently, the association between SAA1 -13T and amyloidosis in Japanese RA patients has been suggested to be the result of an increased transcriptional activity of the gene. 23 Therefore, our data strongly support the notion that the previously reported associations between the SAA1.3 allele and amyloidosis may be accounted for by a strong linkage between -13T and 2995C in the SAA1 gene in Japanese 23,24 Our data also indicate that examining both of the polymorphisms may be more useful than examining just one of them for estimating the risk of the development of amyloidosis. However, because pairwise linkage disequilibrium between polymorphic loci in this gene and the magnitude of the association between these markers and SAA levels have been reported to vary depending on ethnicity, it remains to be seen if the effect of the genetic variant investigated in this study is observed in other ethnic groups to confirm the results of the present study.…”
Section: Discussionsupporting
confidence: 85%
“…Functional studies have demonstrated that the Ϫ13C promoter is responsible for higher transcription rates of SAA1.1 and SAA1.3, respectively (30). However, this does not result in higher serum levels of SAA, probably due to faster clearance of SAA1.1.…”
Section: Prevalence Of Aa Amyloidosis In Rheumatic Diseasesmentioning
confidence: 99%
“…In contrast, single-nucleotide polymorphisms (SNPs) in the 5' flanking region (-13T/C) and in the coding region (2295 C/T and 3010 C/T) of the SAA1 gene constitute risk factors for development of AA amyloidosis in humans. 2,42,43 The finding that all cheetahs have the same SAA1A protein sequence may be an important factor underlying the very high incidence of AA amyloidosis in the cheetah. Further studies are required to characterize the amyloidogenicity of the cheetah SAA1 protein.…”
Section: 35mentioning
confidence: 99%